PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SWASTA NASIONAL YANG TERDAFTAR PADA OTORITAS JASA KEUANGAN (Periode 2016-2021) - A’qilia Munawarah; Siti Rusidah; Rizky Muslim Hidayat (Business Administration, FISIP ULM, 2023)
The overarching goals of this study are to (1) investigate the partial and simultaneous each variable at National Private Commercial Banks (BUSN) licensed by the Financial Services Authority (OJK), and (2) apply the study's findings to a sample of BUSN (2016-2021 period). This study employs a causal-associational approach to quantitative research. The data used to create this summary was collected using a kind of sampling known as